PENGARUH SOCIAL MEDIA MARKETING ACTIVITIES TERHADAP ATTITUDINAL LOYALTY DAN BEHAVIOURAL LOYALTY PADA KONSUMEN OVO - Mikhael Ming Khosasih; Laurentia Verina Halim Secapramana (UNUSA Press, 2021)
This day, social media has been developing. This media was used with company to close with consumer and gain more loyalty to brand. OVO Company have doing many activities in Instagram but the number of active customers not as much as their competitors. Go-Pay have the most active customer with social media activity not as much as OVO. This study aims to discuss the effect of social media marketing activities on OVO customer loyalty from attitudinal loyalty and behavioural loyalty with mediation customer satisfaction and perceived value. This study uses Structural Equation Model (SEM) and 150 respondents processed with SPSS 25 and AMOS 25. The result confirmed that there is positive relation but not significant between OVO customer satisfaction and behavioural loyalty.